Study of Broadband Satellite Customer Behavior Using Costomer Experience Modelling Consumer Segments - Pratama, Gilang Aditya; Tricahyono, Dodie (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
The development of satellite technology in Indonesia has entered the High Throughput Satellite (HTS) era, this technology provides a larger satellite capacity than previous (conventional) technology. This era has been responded positively by satellite operators in Indonesia, one of which is PT. Telkomsat. This condition prompted Telkomsat to release a justification for the manufacture of its first satellite using HTS technology and was launched in February 2024. With this launch, PT. Telkomsat has a total of 5 (five) satellites managed by both its own and partnerships with foreign satellite operators. The decision to fill the empty satellite orbit is not the main factor in the manufacture and launch of satellites, but as an operator with a Vision to become a leading satellite service provider in the Region, Telkomsat continues to increase the leading supply of satellite capacity it has. With the increasing number of satellite operator competitors (opsat) at home and abroad, it presents its own challenges so that the satellite capacity it has can be filled optimally. This phenomenon is a trigger for satellite operators to be able to provide service design innovations that are in demand by the public. This study aims to provide an overview of the customer acquisition strategy (existing competitors or new) of PT Telkomsat's Ku-band HTS using the Customer Experience Modeling (CEM) approach, using three levels of Multilevel Service Design (MSD), namely Value constellation experience (VCE), Service encounter experience (SEE) and Service Experience (SE) so that it can provide a complete conceptualization of the design of broadband satellite services in accordance with the behavior and requirements desired by customers in Papua. This study used a qualitative method with data collection techniques, namely interviews with key informants of broadband satellite customers and supporting informants, then tested for validation and reliability using source triangulation. After conducting this research, the results showed that the consumer segment of satellite broadband customers in Papua Province are still dominated by internet data voucher business activities. This study also found that there are 4 (four) differences in Customer Experience Requirements (CER) that appear between Mangoesky and Ubiqu providers, namely: Affordability, Reliability, Engagement and Speed, the four CERs are used by researchers to develop competitor customer acquisition strategies. From the development of the Strategy Customer Acquisition (SCA) carried out by researchers, the results are expected to provide information and recommendations for PT. Telkomsat is currently going to make various kinds of broadband satellite products using the Ku-band HTS satellite that suits the behavior and desires of broadband satellite customers in Papua Province. Suggestions for further research are to analyze the emergence of starlink in Indonesia against local satellite providers and the calculation of appropriate rates for current broadband satellite products that can accommodate customer requirements. Keywords: High Throughput Satellite (HTS), Customer Acquisition Strategy, Customer Experience Model, Management Strategy, Satellite Communication.